Market research of medicinal products which are used in cardiological diseases treatment - O. S. Kukhtenko; L. S. Simonyan; Ye. V. Hladukh (Zaporozhye State Medical University, 2017)
Aim of the study is to carry out market research of medicinal products which are used in cardiological diseases treatment. Materials and methods. The products range analysis was performed according to the Ukraine State Register of medicines and classification system of ATC. We have studied the pharmaceutical market of cardiotonic action drugs (С01 - cardiological medicines, namely C01ЕВ - other cardiological drugs and С01ЕХ - various combined cardiological drugs). It has been determined that the market of cardiological action preparations is characterized by favorable environment for implementation of the new offered product from the point of view of drugs' economic affordability to consumers. Manufacture leaders of this group of preparations of foreign and domestic production have been denoted. Results of the study. The ratio of medicines trade names of foreign and domestic production is 35 % to 65 %, full dominance of domestic medicines is observed. In the period from 2012 to 2016 the supply of domestic products had increased by 37.6 %, and foreign by 18.6 %. Analysis of registered trade names of medicines by manufacturing companies has shown that the main share of the assortment is formed by drugs of European pharmaceutical companies. Conclusions. Тhe development of domestic production of cardiac funds is a positive factor for the development of drugs in this market segment and it indicates the widespread use of this category of drugs among the population of the country. The analysis of dosage forms was conducted, according to which tablets and liquid dosage forms of a combination composition - tinctures and drops - are the most popular among consumers.